Deciphering Seasonal Patterns in Animal Feeding: A Mechanistic Approach to Analyzing the Restricted Growth of Iberian Pigs - Fernando Sánchez-Esquiliche; Chelo Ferreira; Rosa Nieto; Luisa Ramírez; Gema Matos; Ana Muniesa (Animals)
The growth of animals is influenced by various factors including genetics, nutrition, and environmental conditions. This study focuses on understanding the traditional growth phases of Iberian pigs raised in semi-free-range environments prior to the finishing period within the Mediterranean forest. Using a comprehensive dataset of 5329 pigs, we evaluated the abilities of several mathematical models to predict growth patterns during the early growing and pre-finishing phases. The Gompertz model demonstrated the best fit for the age–weight relationship, indicating its effectiveness in characterizing growth dynamics in these animals. A novel compartmental mathematical model was developed, which integrates age-based estimations for certain body components (protein, water, and ash) with linear body weight predictions for fat. Our findings indicate that this mechanistic model serves as an effective tool for understanding and optimizing management strategies and enhancing growth predictions in traditional pig breeds.